Adsorptive Removal of Nickel Ions by Sodium Alginate-Modified Waste Cotton Fabric - Abedalwafa, Mohammed Awad; Abedelgadir, Ezelarab; Shibraen, Mahmoud HMA (Gezira Journal of Engineering and Applied Sciences; Vol 18 No 2 (2023), 2026)
The development of low-cost adsorbents for the simple and efficient adsorption of metal ions is challenging but of great significance for meeting the strict requirements of environmental protection. The current study focused on the development of a low-cost adsorbent material through the functionalization of waste cotton fabric with sodium alginate (SA), optimization of SA concentration for maximum adsorption of nickel ion, and study of the effects of important parameters such as contact time, pH, initial nickel concentration, and temperature on adsorption performance. The modification was performed by alkaline pre-treatment followed by immersion in different concentrations of SA (0.1- 0.9 wt%). The coating ratio was increased stepwise from 6.1% to 18.3% as the SA concentration increased. The optimum SA concentration was determined, and importantly, the SA-modified waste cotton fabric with 0.7 wt% SA exhibited a high adsorption capacity of 494 mg/g and attained equilibrium in 5 hours. The adsorption performance was pH-dependent, with maximum uptake at pH 6.0. The temperature had little influence on the adsorption efficiency in the range of 20-50°C. Considering the excellent adsorption performance of this modified waste cotton fabric, this simple and novel strategy may open a new avenue for developing sustainable, cost-effective adsorption materials to meet the growing demand for rapid, efficient metal-ion adsorption.